Biofilms in Periprosthetic Joint Infections: A Review of Diagnostic Modalities, Current Treatments, and Future Directions - Shoji, Monica M.; Chen, Antonia F. (The Journal of Knee Surgery, 2020)
As the number of total joint arthroplasties continues to rise, periprosthetic joint infection (PJI), a significant and devastating complication of total joint arthroplasty, may also increase. In PJI, bacterial biofilms are formed by causative pathogens surrounded by extracellular matrix with relatively dormant cells that can persist, resulting in a barrier against the host immune system and antibiotics. These biofilms not only contribute to the pathogenesis of PJI but also result in diagnostic challenges, antibiotic resistance, and PJI treatment failure. This review discusses the development of biofilms and key features associated with biofilm pathogenicity in PJI, current PJI diagnostic methods and their limitations, and current treatment options. Additionally, this article explores novel approaches to treat PJI, including targeting persister bacteria, immunotherapy, antimicrobial peptides, nanoparticles, and bacteriophage therapy. Biofilm eradication can also be achieved through enzymatic therapy, photodynamic therapy, and ultrasound. Finally, this review discusses novel techniques to prevent PJI, including improved irrigation solutions, smart implants with antimicrobial properties, inhibition of quorum sensing, and vaccines, which may revolutionize PJI management in the future by eradicating a devastating problem.
Keywords: periprosthetic joint infection; biofilm; arthroplasty; treatment; prevention